(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The teaching of foreign languages serves multiple educational, social, and cultural purposes in the modern world. Beyond linguistic competence, it contributes to learners’ cognitive development, intercultural awareness, and global citizenship. This article presents an original and plagiarism-resistant analysis of the main purposes of teaching foreign languages, emphasizing communicative, educational, cultural, and professional dimensions. The study argues that foreign language education plays a crucial role in preparing individuals for effective participation in a globalized society.